Hydrogeology and Groundwater Potential in The Sirimau District, Ambon City, Maluku Province - Matrutty, Michelle Theodora; Kololu, Micky; Limehuwey, Resti; Purwoarminta, Ananta; Ulfa, Yuniarti; Jati, Stevandrus Nalendra; Puradimaja, Deny Juanda (BRIN Publishing, 2024)
The demand for clean water in Sirimau District is the highest among all districts in Ambon City, with a total of 14.6 million liters per day for 146,453 people. Moreover, the demand for clean water is increasing with population growth. Therefore, research on hydrogeology and groundwater potential is necessary. The study aims to analyze the discharge and quality of groundwater. The methods used include field surveys, geoelectric measurements, and the analysis of physical and chemical water parameters. The geology of Sirimau district can be divided into five units: Kanikeh Formation, Ultramafic Rock, Ambon Volcanic Rock, Coral Limestone, and Alluvium. Unconfined aquifers are identified in three geological units: the Ambon Volcanic Rock, Alluvium and Coral Limestone, while confined aquifers are in the Ultramafic Rock and the Kanikeh Formation. The water facies are calcium magnesium bicarbonate and sodium-potassium chloride sulfate facies. The groundwater flow in Sirimau District has a northwest flow direction with an average hydraulic gradient of 0.0104. The groundwater discharge in the unconfined aquifer of the Ambon Volcanic Rock is 30 l/s, which is classified as a large discharge. The water quality from physical parameters does not exceed the maximum limit except for three sampling points. In contrast, the chemical content mostly does not exceed the maximum limit except at one drilled well location. Three springs develop due to fractures, while another occurs due to contact.